Pelatihan Penyusunan Laporan Keuangan bagi Guru SMK Akuntansi di Jakarta Barat: Pendekatan e-learning - Sekar Mayangsari; Raditya Mahendrajaya; Ahmad Solahuddin Brillianto (PT. Cendekia Sapta Indonesia, 2023)
Financial Reporting based on IT with Digital-based learning management workshop is the existence of new knowledge that can be applied by teachers during the learning process with their students, especially making questions or quizzes using Google Classroom and Google Forms. The subjects of this workshop are the teachers of the Senior High School – Majoring Accounting (SMK). A digital-based learning workshop for 5 days, namely accounting cycle and financial reporting preparation using ACCURATE including Certification Online learning workshops that have been organized by the Master of Accounting provide new understanding and skills to SMK-Accounting teachers in using ACCURATE as an one accounting software for prepare financial report. The drawback of this activity is the limited facilities and infrastructure available owned by teachers to support digital- based learning, as there are still few teachers who have laptops or computers to support learning and internet signal instability. Contribution of this activity is to support schools to encourage the ability of educators to carry out certification as a skill proved as financial report preparer.